The roles of social media in promoting public health / Nurul Atiqah Kamaruddin…[et.al] - Kamaruddin, Nurul Atiqah; Mat Nor, Nur Liyana; Juahir, Nur Hanani; Mohd Zahari, Nur Syahirah; Gnuawar, Norzafirah; Mohd Abdul Rani, Seri Nazwa (Faculty of Communication and Media Studies, 2016)
Social media can holds considerable potential for health promotion. In promoting health to the public, social media like, Facebook, Twitter and lnstagram can be a very good and easy medium to share about health information. The use of social media increases the potential for easy access to preventive medicine, interaction with health care providers, and public health, hence this will make the health information sharing become easier. The goal of this research is to study the effectiveness and role of social media in promoting public health. This research is using the qualitative research method. An interview has been made to eight informants to get the result for this research. Most of the informants are come from the IT, Medical field and also the social media user. The study found that the social media give many benefits in promoting public health. The benefits include in the aspects of increase the awareness about health, the dissemination of health information and promote healthcare product.